Learning outcomes of an integrated inquiry-based and problem-based learnings for grade 8 science students - Khonkla, Jiratchaya; Thumsiriwat, Jutatip; Supakesorn, Bongkotkorn; Polyiem, Titiworada; Prasertsang, Parichart (Journal of Green Learning, 2024)
The purpose of this study aims to investigate the effects of integrated inquiry-based learning and problem-based learning for improving grade 8 student science learning achievement of force and motion, and to study students’ satisfaction with the learning management plan designed using the integration of integrated inquiry-based learning and problem-based learning. The participants were 39 of grade 8 students from a public school in Thailand. The instruments were a learning management plan designed using the integration of integrated inquiry-based learning and problem-based learning, a 4-multiple choice learning achievement test, and a satisfaction questionnaire. The results of the study showed that there was an improvement in the participants' science learning achievement on the concept of force and motion after implementing the learning management plan. Additionally, the integration of inquiry-based learning and problem-based learning led to increased learning satisfaction among the participants. These findings suggest that the integration of inquiry-based learning and problem-based learning can be an effective approach to teaching science concepts, particularly force and motion, and can lead to improved student learning outcomes and satisfaction.